Layanan Pendidikan Inklusi bagi Anak Berkebutuhan Khusus di Sekolah Buddhis - Pali, Amba; Sukodoyo, Sukodoyo; Medhacitto, Tri Saputra (Universitas Cokroaminoto Palopo, 2025)
The urgency of this research lies in the importance of portraying the actual practices of inclusive education services in a faith-based school, specifically at SD Dharma Mulia, as an effort to foster a learning environment that is friendly, supportive, and adaptive for children with special needs. This research aims to describe inclusive education services at Dharma Mulia Elementary School. The research method uses a descriptive qualitative method with a case study approach. Data collection was done by interview, observation and documentation. The subject in this study were the 3 third-grade students, 1 first-grade teacher, 1 third-grade teacher, the school principal, 2 special needs students in first and second grade, and parents of special needs children. The study's findings encompass three key aspects. Firstly, educators demonstrate a compassionate approach towards children with special needs, offering tailored support such as adjusting intonation, employing diverse teaching strategies and tasks, repeated explanations, varied evaluation methods, and consistent monitoring. Secondly, parents play a crucial role in facilitating their children's learning by participating in their educational journey, overseeing assignments, and providing assistance as needed. Thirdly, peers and the school environment foster inclusivity by offering support and camaraderie, aiding students with disabilities in class, engaging in activities together during breaks, and fostering an environment where all students are treated equally